Sentosa lights of spring : a communications campaign. - Chui, Daphne Yong Xian. (2010)
This report details the collaborative efforts between the authors from Nanyang Technological University Wee Kim Wee School of Communication and Information and Sentosa Leisure Group in promoting the event, Sentosa Lights of Spring 2010. The key strategies conceptualised for this communications campaign are documented. These include research, media relations, marketing and communication tactics, and an overall evaluation of the campaign.The authors approached Sentosa Leisure Group in hopes of collaborating with them on their signature Lunar New Year event.At that point in time, the organisation was in the initial stages of conceptualising Sentosa Lights of Spring, its first night light display event to replace the annual Lunar New Year signature event, Sentosa Flowers. Targeted primarily at families, it was held from 13 to 21 February 2010 during the Lunar New Year period. The authors took on the role of a communications consultancy to complement both the Communications and Marketing departments.